Analysis of the regimes of feedback effects in quantum dot laser. (1st December 2022) - Lu, Ying; Hu, Xiao; Tang, Mingchu; Cao, Victoria; Yan, Jie; Wu, Dingyi; Park, Jae-Seong; Liu, Huiyun; Xiao, Xi; Chen, Siming
Abstract: We investigated the optical feedback effects on the static and dynamic characteristics of 1.3 μ m quantum-dot (QD) Fabry–Pérot laser under reflection from −40 dB up to −8 dB. The onset of coherence collapse is determined as −14 dB from the optical and electrical spectra. Although the degradation in small signal modulation is reported above this critical feedback level, transmission operation with available eye diagram under higher feedback is demonstrated. Under 10 Gb s −1 modulation, there is no obvious degradation in eye diagram regarding the eye shape and extinction ratio up to feedback ratio of −8 dB. The higher feedback tolerance of QD laser under large signal modulation is attributed to the impact of gain compression. This high-speed feedback-resistant operation also indicates that QD laser is a promising light source for isolator-free photonic integrated circuits.